PENGARUH KOMPLEKSITAS PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL , DAN KOMITE AUDIT TERHADAP FEE AUDIT (Studi Kasus Pada Perusahan Manufaktur yang Terdaftar di BEI Tahun 2014-2017) - Napitupulu Benget; Ratnawati Vince; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to analyze the influence of corporate complexity,institutional ownership, and audit committee on audit fees on manufacturingcompanies listed on the Indonesia Stock Exchange in 2014-2017. This study usessecondary data, namely audited financial statements that can be accessed throughthe Indonesia Stock Exchange website www.idx.co.id. The population for thisstudy were 152 manufacturing companies. The sampling method used in this studywas purposive sampling. Based on this method, 39 companies were obtained assamples, with an observation period of 4 years. Thus, the numbers of this study is156 units of analysis. Then the variables in this study were tested using multiplelinear regression analysis using SPSS 24.0. The results of the study showed thatthe complexity of the company and the audit committee had an effect on auditfees. Whereas institutional ownership variable does not have a significant effecton audit fees.Keywords : audit fees, company complexity, institutional ownership, and auditcommittee